Diversification of the Type VI Secretion System in Agrobacteria - Chih-Feng Wu (American Society for Microbiology, 2021)
The T6SS is used by several taxa of Gram-negative bacteria to secrete toxic effector proteins to attack others. Diversification of effector collections shapes bacterial interactions and impacts the health of hosts and ecosystems in which bacteria reside.